PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DI KANTOR KELURAHAN KADIDI KECAMATAN PANCA RIJANG KABUPATEN SIDENRENG RAPPANG - Lukman Lukman; Ani Ardian (Jurnal Bisnis dan Kewirausahaan, 2017)
This study aims to determine the effect of motivation and work discipline on the performance of employees in the office of Kadidi Village, Panca Rijang Sub-district, Sidenreng Rappang Regency. The population in this study amounted to 66 heads of families. Data collection techniques using observation, questionnaires. While the data analysis techniques in this study using SPSS 21. The results of this study is with t count 4.301 ˂ 2,000 (t table) or Sig. 0.000 <0.05 means that motivation significantly influence the performance of employees in Kelurahan Kadidi Panca Rijang District Sidenreng Rappang Regency. Next with t arithmetic 0.715 <2,000 (F table) or sig. 0,477> 0,05 means work discipline does not significantly affect the performance of employees in Kadidi Village Panca Rijang District Sidenreng Rappang Regency. And with F arithmetic 12,977> 3,150 (F table) or sig. 0.000b ˂ 0.05 means that motivation and work discipline significantly influence the performance of employees in Kadidi Village District Panca Rijang Sidenreng Rappang Regency.